Characterization of aortic and brachiocephalic filariasis by Filarioidea sp (Nematoda:Spirurida:Filarioidea) in Mexican ramphastids - Sanchez-Godoy, F.D. (Int J Parasitol Parasites Wildl, 2020)
The manuscript presented herein documents the findings of filaria nematodes in 5 keel-billed toucans, and one emerald toucanet, originated from 2 private aviaries in Mexico City during two years. The birds displayed ruffled feathers, depression, inability to perch, convulsions, and sudden death. Furthermore, thickened wall of the aortic and brachiocephalic arteries, with connective tissue proliferation and chondroid metaplasia were observed. Molecular characterization matched Filarioidea sp (Nematoda: Spirurida: Filarioidea). To the authors’ knowledge, this is the first documented report of filariae Filarioidea sp. causing mortality in ramphastids in Mexico. This manuscript may contribute to expand current knowledge of filariasis and the health risks and livability of wild birds.